Identification and Quantification of Lisinopril from Pure, Formulated and Urine samples by Micellar Thin Layer Chromatography - Bhawani, Showkat Ahmad; Ali, Mohammad; Sharma, S. (Sai Scientific Communications, 2009)
A simple, selective and economical micellar thin layer chromatographic method for on-plate analysis of lisinopril from pure, formulated and spiked urine samples was developed. The proposed method involves use of silica gel H layers as stationary phase and 4% aqueous N-cetyl-N, N, N-trimethylammonium bromide (CTAB) as solvent system. The nature as well as the concentration of surfactants influences the mobility of lisinopril. The effects of alkanols usually used as organic modifiers in the solvent system, pH of the solvent system and the presence of nonelectrolytes (organic) and electrolytes (inorganic) in the solvent system on the mobility of lisinopril were studied. The interference study was carried out by using various organic and inorganic metabolites usually present in human urine. The spectrophotometric determination of lisinopril (pure, formulated and spiked urine) samples was carried out at 595nm using ninhydrin as chromogenic reagent. The beers law is obeyed in a concentration range of 10-150 g/mL with correlation coefficient of 0.9778 and molar absorptivity of 4.083 × 103 mol-1 cm-1. The recoveries of lisinopril (pure, formulated and urine spiked) were within range of 93.0 -100.2% with relative standard deviation ranging from 0.90 -2.8 %.